2014
DOI: 10.1039/c4nr01195c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonding-assisted thermal conduction in β-sheet crystals of spider silk protein

Abstract: Using atomistic simulations, we demonstrate that β-sheet, an essential component of spider silk protein, has a thermal conductivity 1-2 orders of magnitude higher than that of some other protein structures reported in the literature. In contrast to several other nanostructured materials of similar bundled/layered structures (e.g. few-layer graphene and bundled carbon nanotubes), the β-sheet is found to uniquely feature enhanced thermal conductivity with an increased number of constituting units, i.e. β-strands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 41 publications
(50 reference statements)
9
40
0
Order By: Relevance
“…These values are considerably more reasonable for a semicrystalline, protein‐based polymer, such as human hair or a different species of spider . Additionally, molecular dynamics simulations have shown that the β‐sheets (that were the original explanation for the high conductivity of the dragline silk) have a thermal conductivity of only 2–4 W m −1 K −1 , depending on the number of strands in the sheet …”
Section: Resultsmentioning
confidence: 99%
“…These values are considerably more reasonable for a semicrystalline, protein‐based polymer, such as human hair or a different species of spider . Additionally, molecular dynamics simulations have shown that the β‐sheets (that were the original explanation for the high conductivity of the dragline silk) have a thermal conductivity of only 2–4 W m −1 K −1 , depending on the number of strands in the sheet …”
Section: Resultsmentioning
confidence: 99%
“…In these silk proteins, the abundant β-sheet crystals are embedded in a semiamorphous matrix of 3 1 helices and β-turns (Figure 1c), 14 contributing significantly to the physical properties of the silk materials. For instance, our previous study has shown that the thermal conductivity of the poly-alanine (poly-A) β-sheet, 15 an essential building block of the Nephila clavipes spider silk, can be 1-2 orders of magnitude higher than that reported for other protein structures. 16 The main contributor to this phenomenon is the hydrogen bonding between the β-strands (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Atomistic simulations suggest that, in particular, the b-sheets have an unexpectedly high thermal conductivity related to their inter-strand hydrogen bonding. 141 Fully understanding, and emulating, these attributes remains an ongoing pursuit, as research continues to reveal the novel, potentially useful, properties of natural silks beyond their well-known mechanical performance. 142 In the quest of a spider-like silk fiber, it is important to note that reproducing the precise mechanical properties of native spider silk may not necessarily be useful.…”
Section: Discussionmentioning
confidence: 99%